FUNCTIONAL AND SEMANTIC FEATURES OF PROVERBS IN INTERCULTURAL COMMUNICATION (ON THE EXAMPLE OF UZBEK, RUSSIAN AND ENGLISH LANGUAGES) - Saidov Muslimbek Otabekovich (Bright Mind Publishing, 2025)
This article is devoted to a comprehensive study of the functional and semantic features of proverbs in intercultural communication, based on a comparative analysis of the Uzbek, Russian, and English languages. Proverbs, the most important element of any language’s phraseological fund, carry a linguistic and cultural load, reflecting the people’s value system, mentality, historical experience, and social attitudes. In intercultural interaction, they act as a “cultural marker” that can bring people together and cause difficulties in understanding due to differences in the figurative system and cultural code. The article examines the main functions of proverbs - communicative, cognitive, educational, pragmatic, and aesthetic - in a comparative aspect. Particular attention is paid to how universal human concepts receive different linguistic implementation in each culture. The analysis of specific examples demonstrates that despite all the external similarities of the subject matter, proverbs of three languages may differ in the degree of metaphor, lexical content, structure, and cultural imagery. One of the key aspects of the article is the consideration of difficulties arising in the translation and interpretation of proverbs in the conditions of interlingua communication. The author analyzes problems such as the lack of direct equivalents, misunderstanding of cultural realities and symbols, and the possibility of distortion of meaning in literal translation. The thesis is that for successful intercultural interaction, it is necessary to consider both linguistic and extralinguistic (non-linguistic) factors influencing the perception and use of proverbs.
Keywords: Proverb, intercultural communication, functional-semantic analysis, Uzbek language, Russian language, English language, cultural context.